Halimione portulacoides (L.) physiological/biochemical characterization for its adaptive responses to environmental mercury exposure - Anjum, Naser A.
This study investigates largely unexplored physiological/biochemical strategies adopted by salt marsh macrophyte Halimione portulacoides (L.) Aellen for its adaptation/tolerance to environmental mercury (Hg)-exposure in a coastal lagoon prototype. To this end, a battery of damage (hydrogen peroxide, H2O2; thiobarbituric acid reactive substances, TBARS; electrolyte leakage, EL; reactive carbonyls; osmolyte, proline) and defense [ascorbate peroxidase, APX; catalase, CAT; glutathione peroxidase, GPX; glutathione sulfo-transferase, GST; glutathione reductase, GR; reduced and oxidized glutathione (GSH and GSSG, respectively), and GSH/GSSG ratio] biomarkers, and polypeptide patterns were assessed in H. portulacoides roots and leaves at reference (R) and the sites with highest (L1), moderate (L2) and the lowest (L3) Hg-contamination gradients. Corresponding to the Hg-burdens, roots and leaves exhibited a differential modulation of damage- and defense-endpoints and polypeptide-patterns. Roots exhibiting the highest Hg-burden (at L3) failed to maintain a coordination among enzymatic-defense endpoint responses which resulted into increased oxidation of reduced glutathione (GSH) pool, lowest GSH/GSSG (oxidized) ratio and partial H2O2-metabolism. In contrast, the highest Hg-burden exhibiting leaves (at L1) successfully maintained a coordination among enzymatic-defense endpoints responses which resulted into decreased GSH-oxidation, enhanced reduced GSH pool and GSH/GSSG ratio and lower extent of damage. Additionally, increased leaf-carotenoids content with increasing Hg-burden implies its protective function. H. portulacoides leaf-polypeptides did not respond as per its Hg-burden but the roots did. Overall, the physiological/biochemical characterization of below (roots)- and above (leaves)-ground organs (studied in terms of damage and defense endpoints, and polypeptides modulation) revealed the adaptive responses of H. portulacoides to environmental Hg at whole plant level which cumulatively helped this plant to sustain and execute its Hg-remediation potential.